Natural language and possible minds : how language uncovers the cognitive landscape of nature - Mondal, Prakash. (Value Inquiry Book Series, 2017)
In Natural Language and Possible Minds: How Language Uncovers the Cognitive Landscape of Nature Prakash Mondal attempts to demonstrate that language can reveal the hidden logical texture of diverse types of mentality in non-humans, contrary to popular belief. The widely held assumption in mainstream cognitive science is that language being humanly unique introduces an anthropomorphic bias in investigations into the nature of other possible minds. This book turns this around by formulating a lattice of mental structures distilled from linguistic structures constituting the cognitive building blocks of an ensemble of biological entities/beings. This turns out to have surprising consequences for machine cognition as well. Challenging mainstream views, this book will appeal to cognitive scientists, philosophers of mind, linguists and also cognitive ethologists.